Attitude of farmers towards Non-governmental extension organisations in Oyo-State, Nigeria (2013)
The study examined the attitude of farmers towards non-governmental extension organisations (NGEOs) in Oyo State. Multistage sampling procedure was used to choose 160 respondents. Data were collected through interview schedule and analyzed using both descriptive and inferential statistics at p=0.05. More than one-third of the respondents were in the age bracket of 41-50years, majority were maies (67.5%), 76.9% had ten years of formal education and 81.9% were married. Only 28.8% cultivated between 2.43-4.05hectares, 23.7% had more than 2Oyears of farming experience and 65.0% grew cash crop. Majority (86.3%) of the respondents were aware of NGEOs through radio and FADU was ranked 1sl followed by Leveniis as the most prominent NGEOs. Greater percentage (93.7%) was willing to pay for the services of the organizations. However, 82.5% could only afford between N1,000.00~N10,000.00/month. Prohibitive cost of services provided (mean =0.719) was the major limiting factors to respondents' willingness to access services of NGEOs. Notwithstanding, 57.5% had favourable attitude towards NGEOs. There was significant relationship between years of formal education (r=0.346), years of farming experience (r=0.187), marital status (y2=25.47), primary occupation (y2 =10.016) and attitude towards NGEOs. Also, type of crops grown (y2 -4.32), willingness to pay (y2 =9.525), number of hectares under cultivation (r=0.171), source of information (r=0.519) and constraints to using NGOE services (r=0.428) had significant relationships with respondents' attitude towards NGEOs. Synergies and collaboration between governmental and NGEOs become imperative for efficient and effective delivery of extension services